Surface and interface properties of monolayer graphene on hydrophobic and hydrophilic ultrananocrystalline diamond structures for hydrogen sensing applications. (22nd January 2022) - Saravanan, Adhimoorthy; Huang, Bohr-Ran; Kathiravan, Deepa
Abstract: Here, for the first time, we synthesize hybrid hydrophilic and hydrophobic nanocarbon materials with reliable and stable gas sensing performance. The hybrid monolayer graphene (Gr)–nitrogen and argon (N2 and Ar) gas incorporated ultra-nanocrystalline diamond (Gr/N2 @UNCD and Gr/Ar@UNCD) structures were synthesized using a microwave plasma enhanced chemical vapor deposition (MPECVD) method. The presented nanohybrid combinations have a unique morphology with diamond defects (sp 3 ) covered by a graphene sheet (sp 2 ). Sample sensors with metal electrodes were fabricated to study the H2 gas sensing properties of the material. Thus, the as-fabricated Gr/N2 @UNCD exhibited higher sensor response (14.6%) than those of the as-fabricated Gr, N-UNCD and Gr/Ar@UNCD (3.6, 1.07 and 11.2%) based devices. The Gr/N2 @UNCD nanohybrid based sensor showed outstanding repeatability, selectivity and stability over ∼56 days. The substantial improvement in the H2 sensing performance of the as-fabricated Gr/N2 @UNCD nanohybrid based sensor was attributed to the modifications in surface morphology and resistance. The partial-hydrophobic surface of Gr/N2 @UNCD alters the beneficial resistivity and improved absorption, which assists in the efficient transport of electrons and H2 gas molecules. The hybrid nanostructure of Gr-N2 @UNCD exhibits several unique properties that paves the way to future opportunities for advanced gas sensor fabrication. Graphical abstract: Image 1 Highlights: For the first time, H2 sensing of Graphene-UNCD hybrid materials was studied. The Gr/N2 @UNCD hybrid sensor offers excellent response of 14.6%. The hydrophobic surface of Gr/N2 @UNCD assists in enhanced sensing properties. Present sensor exhibits outstanding repeatability and stability for 56 days.